2012
DOI: 10.4049/jimmunol.1101224
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Augments IL-10 Production by Microglial Cells through an A2B Adenosine Receptor-Mediated Process

Abstract: Microglia are activated by pathogen-associated molecular patterns and produce pro-inflammatory cytokines, such as TNF-α, IL-6, and IL-12, and the anti-inflammatory cytokine IL-10. Adenosine is an endogenous purine nucleoside and is a ligand of four G protein-coupled adenosine receptors (ARs), which are the A1AR, A2AAR, A2BAR and A3AR. ARs have been shown to suppress TNF-α production by microglia, but their role in regulating IL-10 production has not been studied. Here, we demonstrate that adenosine augments IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 63 publications
1
69
0
3
Order By: Relevance
“…We also consider the report of direct regulation of expression of IL-10 by NFkB (Cao et al, 2006). Our data suggest an alternative explanation of how the A 2B AR could regulate IL-10 production through A 2B AR-dependent NFkB signaling, in addition to the A 2B AR-p38-CREB pathway reported by Koscso et al (Koscsó et al, 2012).…”
Section: Discussionmentioning
confidence: 72%
“…We also consider the report of direct regulation of expression of IL-10 by NFkB (Cao et al, 2006). Our data suggest an alternative explanation of how the A 2B AR could regulate IL-10 production through A 2B AR-dependent NFkB signaling, in addition to the A 2B AR-p38-CREB pathway reported by Koscso et al (Koscsó et al, 2012).…”
Section: Discussionmentioning
confidence: 72%
“…On microglia, van der Putten et al reported A 1 , A 2A and A 3 receptor expression, but not A 2B (van der Putten et al, 2009), whereas a more recent report revealed the presence of the A 2B receptor on microglia, and an important role for this receptor in augmenting the production of the cytokine, IL-10 ( Koscso et al, 2012). The difficulty in ascertaining P1 subtype expression on specific cell types lies in the possible introduction of experimental artifacts from cell culture methods, detection limits associated with anatomical methods and specificity issues relating to physiological approaches using pharmacological tools.…”
Section: The Role Of Adenosine In Neuroinflammationmentioning
confidence: 99%
“…Optimal Induction of IL-10 by LPS Requires P38 MAPK Activity-MAPKs, including ERK and p38 MAPK, play a role in the regulation of IL-10 production in different systems such as TLR-triggered signals (22,23). Since ␤-arrestin 2-deficient significantly disturbed both p38 activation and IL-10 production following LPS stimulation (Figs.…”
Section: ␤-Arrestin 2 Deficiency Impairs Il-10 Production Inmentioning
confidence: 99%